Pengaruh Suhu Air terhadap Densitas dan Karakteristik Mikroplastik Teh Celup Kemasan Produk Komersial dan Pemanfaatannya sebagai Book Chapter - Egita Zahratul Jannah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
In Indonesia, tea bag consumption is very high due its easy and simple to brew. However, this simplicity can increase the risk of exposure to microplastics from the packaging material during the brewing process. The lack of clear scientific information regarding the quantity, characteristics, and effect of air temperature on microplastic release is an important basis for this research. Therefore, this study aims to analyze the effect of water temperature on the density and characteristics of microplastics in commercial teabag brewing water and its use as a book chapter. The experiment used in this study used three types of treatments with three brewing temperature, namely P1 (80°C), P2 (90°C), and P3 (100°C), as well as positive control treatments (K+) and negative control (K-). The samples used were commercial teabag products from three product variants with the observed parameters were the density of microplastic fragments, size, shape, color, and type of microplastic fragments analyzed using FTIR (Fourier Transform Infrared Spectroscopy). The results showed that temperature affected the release of microplastics, namely the higher the water brewing temperature, the more microplastics were released, especially in the Sc variant (29.33 ± 3.61 fragments). The most common microplastic fragments found were <1000 μm in size, with the dominant shape was fiber, and the dominant color being red. FTIR analysis showed that the resulting microplastic fragments were polyamide (nylon). This was indicated by the functional groups detected, which were predominantly characteristic of nylon, namely N-H stretch. The conclusion of this study was that the higher the water brewing temperature, the more microplastics were released. The results of this research were then successfully developed into a book chapter, which was declared valid by the validator for public reading
FINALISASI oleh Arif 2026 Mei 26
Keywords: brewing process; FTIR analysis; polyamide (nylon)